Community social determinants and health outcomes drive availability of patient-centered medical homes. (January 2021) - Bell, Nathaniel; Wilkerson, Rebecca; Mayfield-Smith, Kathy; Lòpez-De Fede, Ana
Abstract: The collaborative design of America's patient-centered medical homes places these practices at the forefront of emerging efforts to address longstanding inequities in the quality of primary care experienced among socially and economically marginalized populations. We assessed the geographic distribution of the country's medical homes and assessed whether they are appearing within communities that face greater burdens of disease and social vulnerability. We assessed overlapping spatial clusters of mental and physical health surveys; health behaviors, including alcohol-impaired driving deaths and drug overdose deaths; as well as premature mortality with clusters of medical home saturation and community socioeconomic characteristics. Overlapping spatial clusters were assessed using odds ratios and marginal effects models, producing four different scenarios of resource need and resource availability. All analyses were conducted using county-level data for the contiguous US states. Counties having lower uninsured rates and lower poverty rates were the most consistent indicators of medical home availability. Overall, the analyses indicated that medical homes are more likely to emerge within communities that have more favorable health and socioeconomic conditions to begin with. These findings suggest that intersecting the spatial footprints of medical homes in relation to health and socioeconomic data can provide crucial information for policy makers and payers invested in narrowing the gaps between clinic availability and the communities that experience the brunt of health and social inequalities. Highlights: Whether Patient-Centered Medical Homes emerge within socially vulnerable communities that would benefit from integrative care is unknown. We found that medical home density was inversely associated with measures of social vulnerability, particularly community uninsured rates. Communities with the greatest influx of medical homes are more likely to have favorable health and socioeconomic conditions to begin with.